The intelligence battle in the Gulf of Guinea: Espionage and counter-espionage operations in Spanish Guinea - Abba, Saliou (Scientia Militaria - South African Journal of Military Studies, 2022)
The study, on which this article is based, focused on the redistribution of geopolitical maps that took place in sub-Saharan Africa after the advent of the Third Reich, which resulted in the institutionalisation of the practice of intelligence in the Gulf of Guinea. This historical plot testifies to the clash between the colonial branches of the British, German and United States intelligence services through clandestine operations in the Spanish Guinean colony. Addressing the issue of the perception of Spanish Guinea by the intelligence services of the various belligerent European powers, this article highlights the factors behind the apprehension of sub-Saharan Africa as a theatre of operations in the Second World War. The archival sources and the bibliographic data analysed from the perspective of Intelligence Studies, revealed the consideration of the colony of Spanish Guinea as a target of paramount importance by the German, French, British and American units in charge of the underground war, an offensive strategy, which inaugurated a new paradigm from military and security view points for Cameroon under the League of Nations trusteeship.